Analisis break event point biaya pendidikan (penelitian di MA baitul hikmah-haurkuning, kab. tasikmalaya) - Asy`arie; Dwi Ajeng Maulidya Makalao; Dienha Habibie; Badrudin; Qiqi Yuliati Zakiah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
This study aims to explore and understand the phenomenon of educational financing in Islamic boarding schools (pesantren) through Break Even Point (BEP) analysis. This research employs a qualitative approach using a case study method, which enables an in-depth understanding of financial management practices in real-life contexts. The primary focus of this study is the perspective of pesantren managers in managing educational costs and the strategies implemented to achieve the break-even point. Data were collected through in-depth interviews, observations, and documentation to enhance the validity and credibility of the findings. The data analysis was conducted using a thematic approach, including data organization, coding, and the identification of key themes. The findings reveal that pesantren managers face various challenges in managing educational costs, such as limited financial resources, fluctuating student enrollment, and increasing operational needs. To address these challenges, managers implement several strategies, including budget efficiency, diversification of income sources, and optimization of available resources. This study is expected to contribute to the development of financial management practices in pesantren and to enrich the literature on Islamic education, particularly in the area of sustainable educational financing.